Vlasta, Ancient Czech Myths and the Myth Reinterpretation: An Interview with the Documentary Filmmaker Hana Železná - Jonssonová, Pavla (Iluminace, 2008)
An interview with Czech documentary filmmaker and experimental film director Hana Železná about her film Má Vlasta.
Keywords: Má Vlasta 2008; Czech directors; experimental films; feminism